T62. Bilateral independent periodic discharges are associated with electrographic seizures and poor outcome: A case-control study. (May 2018) - Osman, Gamaleldin M.; Rahangdale, Rahul; Britton, Jeffrey; Gilmore, Emily; Haider, Hiba A.; Hantus, Stephen; Herlopian, Aline; Hocker, Sara; Lee, Jong Woo; Legros, Benjamin; Punia, Vineet; Rampal, Nishi; et al.
Abstract : Introduction: Bilateral independent periodic discharges (BIPDs) is an increasingly recognized EEG pattern in the critically ill but its clinical correlates, and association with electrographic seizures and outcome are uncertain. Methods: A retrospective case-control study of patients with BIPDs compared to two control groups, one without periodic discharges ("No PDs") and one with lateralized periodic discharges on only one side ("LPDs"), all matched for age, etiology and level of alertness. Univariate and multivariate statistics were applied. Results: 85 cases and 85 controls were included in each group. The most frequent etiologies of BIPDs were ischemic and hemorrhagic strokes (25%), CNS infections (10%), and anoxic brain injury (10%). 77 (91%) patients with BIPDs had stupor or coma, including 31% in coma. Electrographic seizures were more common in the BIPDs group than No PDs group (45% vs. 8%; p  < 0.0001), but similar to the LPDs group (52%). In-hospital mortality rate was higher in the BIPDs group (36%) than in the No PDs group (18%; p  < 0.001). Fewer patients with BIPDs achieved good outcome (moderate disability or better; 18% vs. 36%; p  < 0.001). Outcome was similar among LPDs and BIPDs groups (24% mortality, 26% good outcome). In multivariate analyses, BIPDs (OR: 3.0 [1.4–6.4]) and coma (OR: 6.8 [3.1–14.7]) were independently associated with mortality; and BIPDs (OR: 2.9 [1.4–6.2]), coma (OR: 3.6 [1.5–9.2]) and age ⩾ 65 years (OR: 2.7 [1.3–5.7]) were independently associated with poor outcome. Conclusion: In this retrospective case-control study, BIPDs were most frequently seen due to bilateral or diffuse acute brain injury, and were associated with a higher risk of electrographic seizures and worse outcome than a matched group with no PDs. Outcome was similar to those with LPDs. Further studies are needed to assess the independent effect of BIPDs on brain injury and outcome.